Structural, morphological and optical properties of sprayed Cu2ZnSnS4 thin films by varying the molar concentration of Zn & Sn. (January 2019) - Chandel, Tarun; Zaman, M. Burhanuz; Dwivedi, Shailendra Kumar; Poolla, Rajaram
Abstract: In this study, nanocrystalline thin films of Cu2 Zn1-x Sn1+x S4 and Cu2 Zn1+x Sn1-x S4, (x = 0.15, 0.28 and 0.39) were deposited on glass substrates at 300 °C by the spray pyrolysis technique. The effect of molar variation of zinc and tin on the structural, morphological and optical properties of CZTS films was investigated. X-ray diffraction patterns and Raman spectroscopy reveal that all the films crystallise in the tetragonal phase of the kesterite structure with preferential orientation along 〈1 1 2〉 direction without any secondary phases. The preferred orientation of crystallites in CZTS films remains unchanged as the composition is changed, although a slight shift in (hkl) planes occurs, resulting from the variation in lattice parameters. Morphological analysis reveals that the films are uniformly covered with nanoplates of various sizes. EDAX studies show that elemental variation in the grown films is similar to the ionic compositional variation taken in the spray solution. The films possess marginal non-stoichiometry in [ C u ] / [ Z n + S n ] composition from 0.98 to 1.06. Optical studies show that the band-gap lies in the range of 1.45 eV–1.58 eV, indicating the material has absorbing properties suitable for photovoltaic applications. Highlights: Sprayed Cu2 Zn1-x Sn1+x S4 and Cu2 Zn1+x Sn1-x S4 thin films were grown at 300 °C. Band-gap tuning is observed in Cu2 Zn1-x Snx S4 and Cu2 Zn1-x Snx S4 thin films. XRD and Raman studies reveal that the synthesized material is pure CZTS.